Legal Due To The Subject Limitation Of Liability Rights - Irmawati Irmawati; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This research aims (1) To find out the legal consequences of limiting the subject of the mortgage provider for the enforcement of Article 9 paragraph (5) of the Regulation of the Minister of ATR / BPN Number 9 of 2019 concerning Electronic Mortgage Services. This study uses an Empirical juridical approach. This study concludes (1). The legal consequence of the limitation on the subject of the Granting of Mortgage Rights on the enforcement of Article 9 paragraph (5) of the Regulation of the Minister of ATR / BPN Number 9 of 2019 concerning Electronic Mortgage Services, namely the defective element of intention in APHT, the emergence of nominee agreements and PERMEN ATR / BPN No. 9/2019 contradicts the principle of lex superiori derogat legi inferiori Article 8 in conjunction with Article 4 paragraph (4) and paragraph (5) of the UUHT.